Migration policy can boost PISA results: Findings from a natural experiment - Maria Alejandra Cattaneo; Stefan Wolter (Institute for the Study of Labor (IZA), 2012)
Switzerland radically changed its migration policy in the mid-nineties from a non-qualified only policy to one that favors the immigration of highly qualified migrants. To analyze the impact of this change on the schooling outcomes of migrants, this paper compares the PISA (OECD Programme for International Student Assessment) results from 2000, which were not yet affected by the change in the migration policy, with the PISA 2009 test. Using a Blinder-Oaxaca decomposition analysis, we find that almost 70% of the 43-point increase (more than one standardized school year) in the PISA scores of first-generation immigrant students in an environment with stagnant Swiss PISA results was due to changes in the individual background characteristics of the new immigrants (direct effect) and improved school composition (lower shares of students who did not speak the testing languages as an indirect effect). The indirect effects also indicate that internationally comparative analyses should more fully consider differences in national migration policies when assessing the success of migrant integration.
urn:nbn:de:101:1-201204239403
Keywords: I21; I24; J15; 330; Blinder-Oaxaca decomposition; migration; natural experiment; PISA; Migrationspolitik; Hochqualifizierte Arbeitskräfte; Wirkungsanalyse; Bildungsniveau; Feldforschung; Schweiz